Prevalence and Risk Factors of Neglected Tropical Diseases Among Women and Children in Rural Liberia: A Regional Perspective - J. Samuel Kamanda; Atul Khajuria; Eric Kwasi Elliason; Stephen Monday (Recent Trends in Infectious Diseases, 2025)
Neglected Tropical Diseases (NTDs) remain a critical public health challenge in Liberia, disproportionately affecting women and children in rural regions due to systemic inequities in water, sanitation, and healthcare access. This cross-sectional study assessed the prevalence and risk factors of NTDs among 1,000 participants (600 children above 15 years and 400 women aged 15–49) in rural Liberia using stratified and cluster sampling. Laboratory diagnostics, including Kato-Katz stool analysis, urine filtration, and rapid antigen testing, revealed an overall NTD prevalence of 78%, with children bearing the highest burden (85.8%) compared to women (66.3%). Schistosomiasis (31%), soil-transmitted helminths (27.5%), and lymphatic filariasis (19.5%) were the most prevalent diseases. Key risk factors included open defecation (aOR: 3.2; 95% CI: 1.8–5.6), lack of footwear (aOR: 2.8; 95% CI: 1.5–4.9), and poor water access (aOR: 2.1; 95% CI: 1.2–3.7). The findings underscore the intersection of environmental exposure, gender roles, and infrastructural neglect in perpetuating NTD transmission. Children are particularly susceptible to neglected tropical diseases (NTDs) due to both behavioral habits—such as playing in contaminated environments—and underdeveloped immune systems. Similarly, women often face increased exposure risks because of their caregiving responsibilities and certain occupational roles, even though they may report lower infection rates. There is a pressing need for comprehensive interventions, including the development of clean water and sanitation systems, community-based health education, and the continued implementation of mass drug administration. This study highlights the importance of adopting strategies that are sensitive to gender dynamics and resilient to climate-related challenges in order to reduce Liberia’s NTD burden. Such efforts are essential to meeting the global target of eliminating NTDs by the year 2030, as outlined in the Sustainable Development Goals.
Keywords: Liberia; Lymphatic Filariasis; Neglected Tropical Diseases; Rural Health; Schistosomiasis; Soil-Transmitted Helminths; WASH Interventions; gender disparities